Interaction of Chitosan with mono and di- valent anions in aqueous solution studied by cyclic voltammetry at a water/1,2-dichloroethane interface - Riva, Jullieta Soledad (2011)
The interaction of the cationic polyelectrolyte chitosan (CHI), of different molecular weights, with two anions, picrate (Pi−) and eosin (Eo2−), in water was analyzed at pH 2.50 and 5.00. For this purpose the anions transfer current across a water/1,2-dichloroethane interface was employed to quantify anions concentration in absence or in presence of CHI. When CHI was added in increasing amounts to aqueous solutions containing Eo2− or Pi−, a gradual decrease in current values was observed, evidencing the binding ofthe anions to the polymer. This effectwasmore important atlowpH values and for CHIwith the highest molecular weight. From the results it is concluded that the interaction Eo2−-CHI is stronger than the corresponding to Pi−, probably due to the higher negative charge, and therefore themore pronounced hydrophilic nature of the ﬁrst anion, which could lead to favour the electrostatic interactions with the cationic polyelectrolyte.